Granuloma necrosis during Mycobacterium avium infection does not require tumor necrosis factor - Florido, M (2004)
The infection of tumor necrosis factor (TNF)-deficient mice with low doses of the virulent Mycobacterium avium strain 25291 led to the appearance of necrotic granulomas at 93 days of infection, i.e., sooner than necrotic granulomas appeared in C57BL/6 animals. Additionally, TNF-deficient mice exhibited higher mycobacterial loads in the infected organs, had extremely exacerbated gamma interferon responses as evaluated in the sera of infected animals, and showed reduced survival. Thus, TNF is not required for granuloma necrosis.